The use of maize and poplar in chelant-enhanced phytoextraction of lead from contaminated agricultural soils - Komárek, Michael; Tlustoš, Pavel; Száková, Jiřina; Chrastný, Vladislav; Ettler, Vojtěch (Chemosphere, 2007)
Chelant-enhanced phytoextraction of heavy metals is an emerging technological approach for a non-destructive remediation of contaminated soils. The main objectives of this study were (i) to assess the extraction efficiency of two different synthetic chelating agents (ethylenediaminetetraacetic acid (EDTA) and ethylenediaminedisuccinic acid (EDDS)) for desorbing Pb from two contaminated agricultural soils originating from a mining and smelting district and (ii) to assess the phytoextraction efficiency of maize (Zea mays) and poplar (Populus sp.) after EDTA application. EDTA was more efficient than EDDS in desorbing and complexing Pb from both soils, removing as much as 60% of Pb. Maize exhibited better results than poplar when extracting Pb from the more acidic (pH approximately 4) and more contaminated (up to 1360 mg Pb kg(-1)) agricultural soil originating from the smelting area. On the other hand, poplars proved to be more efficient when grown on the near-neutral (pH approximately 6) and less contaminated (up to 200 mg Pb kg(-1)) agricultural soil originating from the mining area. Furthermore, the addition of EDTA led to a significant increase of Pb content especially in poplar leaves, proving a strong translocation rate within the poplar plants.
Keywords: biomasa; olovo; Agriculture; Lead; Biodegradation, Environmental; chelátory; Biomass; kukuřice setá; Populus; Chelating Agents; Ethylenediamines; Mining; látky znečišťující půdu; ethylendiaminy; Soil; průmyslový odpad; Soil Pollutants; Succinates; zemědělství; Zea mays; hornictví; Edetic Acid; Industrial Waste; sukcináty; Financing, Organized; půda; financování organizované; biodegradace; EDTA